Regarding the World Health Day - Anays de la Caridad Núñez Herrera; Ana Teresa Fernández Vidal (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
When a Cuban family doctor knows about the access and universal health coverage, it is something so close that it is almost impossible to value these words.; however considering them becomes extraordinary when accomplishing an international collaboration task , where poverty and inequalities persist. In this work It is reflected on the solid health strategy developed by Cuba, an underdeveloped country, whose policy has allowed to fulfill the wish of health for everyone, having as a base the Primary Health Care System.